Phylogeography and conservation genetics of endangered saproxylic beetles in Europe - Drag, Lukáš (Jihočeská univerzita, 2016)
This thesis introduces the use of molecular methods for the conservation of several species of endangered saproxylic beetles in Europe. It focuses on the questions related to the DNA preservation and microsatellites development, as well as the evolutionary history and conservation of threatened species. Using the combination of mitochondrial and nuclear markers, the genetic diversity and reintroduction history of Cerambyx cerdo was assessed and the phylogeography of Rosalia alpina from the whole range of its distribution was studied. This information is valuable for designing more efficient conservation strategies.
Phylogeography and conservation genetics of endangered saproxylic beetles in Europe
Keywords: insect ecology; Natura 2000; Coleoptera; Osmoderma barnabita; Europe; mtDNA; cytochrom c oxidase; beech forest; Fagus sylvatica; population genetics; insect ecology; Natura 2000; Coleoptera; Osmoderma barnabita; Europe; mtDNA; cytochrom c oxidase; beech forest; Fagus sylvatica; population genetics